A Historical Case of Anglo-Ottoman Musical Interactions: The English Autopiano of Sultan Abdulhamid II - Kutlay, Evren (SAGE PUBLICATIONS LTD, 2019)
Initiated by Queen Elizabeth I upon sending the Ottoman Sultan Mehmed III an organ, Anglo-Ottoman music-historical relations date back to the sixteenth century. Such interactions continued during the Nizam-i Cedid (New Order) period of the eighteenth century and became more frequent in the nineteenth century, during the modernization movement of the Ottomans. After the establishment of the Muzika-yi Humayun (The Imperial Music School), the Ottoman Empire began to import many European musical instruments, including pianos, to Ottoman lands. To this end, some English piano manufacturers became the main piano suppliers of the Ottoman Empire. Among them was Kastner & Co. Ltd. According to two archival files identified in the Turkish Prime Ministry Ottoman Archives in Istanbul, an autopiano was bought for Sultan Abdulhamid II from Kastner & Co. of London in 1907. The files include the receipt of the shipped equipment, its description, and a user's manual, as well as diplomatic manuscripts about the event. This article summarizes the history of Anglo-Ottoman musical interactions up until this historical trade and analyses these archival files within their historical and cultural contexts.
Keywords: Anglo-Ottoman musical interactions; autopiano; English piano suppliers of the Ottomans; Kastner & Co; Ltd; pianos; Ottoman piano; Westernization; History; Government & Law